Good governance strategy in maintaining the national interest of state defense: a study in the North Natuna sea region - Theo L Sambuaga; Amarulla Octavian; Asep Adang Supriyadi; I. Gede Sumertha (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
"Good governance" reforms public sectors in several nations. Science is also investigating good governance. Researchers see good governance differently. Lawmakers stress state defense. Indonesia's maritime issues endanger defense. Indonesia bolstered its military after China unilaterally claimed the North Natuna Sea with its nine-dash line (NDL). The Indonesian government must strengthen the military since this move affects the area. This study fills gaps in thinking by reviewing national journal publications on good governance options for the North Natuna Sea's potential threat. This research uses soft and hard ways to describe how the Indonesian government controls potential conflict in the South China Sea, which would affect the North Natuna Sea region. Good governance comprises the central government's coordination and collaboration with the local government of Riau Islands Province, where the North Natuna Sea is located, and how well this local government meets its population's requirements in accordance with central government policies. The state defends the South China Sea using physical power and soft power diplomacy, which inspired this research (soft power). Develop and restore boundaries to rule successfully. Hence, improving lives achieves government goals. This government commitment requires Natuna Sea community and stakeholder cooperation. Thus, this research admits advises more further investigation.